How do you do this linear system? {3x+y+2z=3 X-2y+3z=1 4x-8y+12z=7

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

How do you do this linear system? {3x+y+2z=3 X-2y+3z=1 4x-8y+12z=7

Mathematics
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

is it matrices or which topic
Look at equation 1 where you see the term 1y or just y isolate that y to get 3x+y+2z=3 y=3-3x-2z
now go to the other 2 equations and replace y with 3-3x-2z

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

let @jim_thompson5910 take care of that
so equation 2 goes from x-2y+3z=1 to x-2(3-3x-2z)+3z=1 x-6+6x+4z+3z = 1 7x-6+7z = 1 7x+7z = 1+6 7x+7z = 7 7(x+z) = 7 7(x+z)/7 = 7/7 x+z = 1
oh my
Now focus on Equation 3 4x-8y+12z=7 4x-8(3-3x-2z)+12z=7 4x-24+24x+16z+12z=7 28x-24+28z=7 28x+28z=7+24 28x+28z=31
After doing all that, things boil down to these 2 equations x+z = 1 28x+28z=31
use any method to solve that new system of equations for x and z once you have x and z, you can use them both to find y

Not the answer you are looking for?

Search for more explanations.

Ask your own question